Leadership Communication and Implications For Acceptance of The Go-Biz Application By MSMEs Employees (Case Study: Bogor District) - Nadia Nur Soraya; Sarwititi Sarwoprasodjo; Irman Hermadi (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Leaders of micro, small, and medium enterprises (MSMEs) have a role in the continuity of a business. Purpose: This research aims to examine the influence of leadership communication on the acceptance of the Go-Biz application by MSME employees in Bogor Regency. Design/methodology/approach: Research on acceptance of the Go-Biz application by MSME employees in Bogor Regency uses the Technology Acceptance Model theory modified by the Motivating Language Theory. This type of research is quantitative, using primary data. Research data was collected through structured interviews using questionnaires and direct field observations. The sampling technique is accidental sampling. The research population is 100 MSME employees who use the GoBiz application and are located in the Bogor Regency area. Inferential data analysis used PLS SEM 3 analysis.Findings/Result: The research results showed that the influence of leadership communication on the acceptance of Bogor Regency MSME employees in the Go-Biz application consisted of language giving direction, language making meaning, perception of usefulness, perception of ease, attitude of use, and actual use. Direction-giving language, namely explaining the benefits of the application, application instructions, and information on the achievements obtained, and meaning-making language consisting of telling the importance of the application and suggestions for use, are factors that influence the acceptance of the Go -Biz application by Bogor district MSME employees.Conclusion: Effective leadership in communication will help articulate the MSME vision and strategy regarding the development and implementation of application technology. This helps the entire team understand the direction the MSME is taking in terms of technology. Additionally, strong leadership through communication can motivate teams to accept new technologies and actively contribute to their development or use.Originality/value (State of the art): There has been no research that examines the influence of the three motivational languages (motivating language theory) that leaders can use to communicate more effectively in the workplace regrading employee acceptance of an application using the Technology Acceptance Model (TAM) theory. Keywords: leadership communication, motivational language theory, technology acceptance model, MSMEs (Micro, Small, and Medium Enterprises)